(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The world of education at this time faces many challenges in various fields. Not all educational programs at the elementary school level utilize information technology. The development of technology at this time greatly influenced the learning styles of elementary school children. Starting from the use of learning media to the learning process. Meanwhile, educators can only deliver material teaching materials character verbally and not systematically and are not supported by good learning media. To support it all, we need a learning model that solidifies information technology and is by the character of students and educators. This is done so that the character teaching materials can be delivered properly by educators and responded well by students. In line with the above background, hyper content-based learning models can be developed as one solution to help educators deliver character education materials. The development model used is Hannafin and Peck’s model which consists of three stages, namely: Need Assessment (Design Analysis Phase), Design (Design Phase), and Develop / Implement (Development and Implementation Phase). The result of this research is the integrity character learning model for elementary school children based on hyper content.